SERS Imaging of Cell‐Surface Biomolecules Metabolically Labeled with Bioorthogonal Raman Reporters. Issue 8 (18th June 2014) - Xiao, Ming; Lin, Liang; Li, Zefan; Liu, Jie; Hong, Senlian; Li, Yaya; Zheng, Meiling; Duan, Xuanming; Chen, Xing
Abstract Live imaging of biomolecules with high specificity and sensitivity as well as minimal perturbation is essential for studying cellular processes. Here, we report the development of a bioorthogonal surface‐enhanced Raman scattering (SERS) imaging approach that exploits small Raman reporters for visualizing cell‐surface biomolecules. The cells were cultured and imaged by SERS microscopy on arrays of Raman‐enhancing nanoparticles coated on silicon wafers or glass slides. The Raman reporters including azides, alkynes, and carbondeuterium bonds are small in size and spectroscopically bioorthogonal (background‐free). We demonstrated that various cell‐surface biomolecules including proteins, glycans, and lipids were metabolically incorporated with the corresponding precursors bearing a Raman reporter and visualized by SERS microscopy. The coupling of SERS microscopy with bioorthogonal Raman reporters expands the capabilities of live‐cell microscopy beyond the modalities of fluorescence and label‐free imaging.